(untitled) (International Journal of Engineering and Computer Science, 2024)
Current studies on behavioural biometrics authentication have been focused on the use of deep learning and keystroke dynamics but the aspect of conscious optimization of the algorithm in order to obtain best outcome has not been considered. This study employed and incorporated Bayesian algorithm into Recurrent Neural Network to build a Keystroke Behavioural Biometric (KBB) authentication model used against social engineering attacks. The model begins with importing the keylogging dataset for data pre-processing, feature extraction, and RNN algorithm was used to build the KBB model. Hyperparameter tuning was done to achieve optimal results. A traditional optimizer called Adaptive Momentum Estimation (Adam) was used and evaluated so as to estimate the impact of optimization in model inferencing. RNN model result with Bayesian optimization technique shows a better performance than the result of RNN model with ADAM optimization. The essence of incorporating and evaluating the best optimization technique is to come up with an effective and accurate model for behavioural biometric authentication, that could mitigate effectively against social engineering attacks.